Bone metastases dosimetry for 223RA-dichloride: An italian multicenter study. (September 2016) - Pacilio, Massimiliano; Cassano, Bartolomeo
Abstract : Purpose: In-vivo macrodosimetry of bone lesions in 223 Ra-dichloride therapy is feasible, but the possibility of personalised treatments requires further research. Multicenter studies are powerful tools to investigate the role of dosimetry, but the standardization of dosimetric procedures should be guaranteed, to assure data comparability. Recently, a multicenter study in this context was proposed in Italy, and calibration protocol of gamma cameras, criteria for patients' eligibility, and dosimetric methodologies are currently under investigation. Methods: The sensitivity of some gamma cameras (3/8-inch crystal, MEGP collimators) for 223 Ra was measured in air, varying activity, source-detector distance, and source diameter. Transmission curves were measured for attenuation/scatter correction with the pseudo-extrapolation number method, varying the experimental setup. The lesions visibility on 223 Ra images was studied by univariate ROC analysis (25 patients, 69 lesions), considering visible/non visible lesions as true positive/true negative group, and using as score value the lesion/soft tissue contrast ratio (CR) derived from 99m Tc-MDP WB scan. Results: Sensitivity was nearly constant varying activity and distance, and for object area ⩾960 mm 2 . Transmission curves are affected by experimental setup and source size, leading to activity quantification errors up to 20%. The ROC analysis yielded an AUC of 0.972 and an optimal threshold of CR of 10, corresponding to an accuracy of 92%. Conclusion: The minimum calibration protocol requires sensitivity and transmission curves measurements varying the object size. Lesions with 99m Tc-MDP CR higher than 10, not overlapping the GI tract, are generally visible on223 Ra images at 24 h, and thus eligible for dosimetric studies.